Capsules for gastrointestinal sampling
The capsule-based device with a biodegradable coating and sampling hydrogel addresses the limitations of current digestive sampling technologies by enabling non-invasive, targeted sampling across the GI tract, including the colon, enhancing diagnostic accuracy and patient comfort.
Patent Information
- Application Number
- JP2024554906
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-17
- Filing Date
- 2023-03-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-03-07
AI Technical Summary
Current technologies for digestive sampling, particularly in the gastrointestinal tract, face challenges such as invasiveness, limited sampling accuracy, and inability to target specific regions like the colon, which is crucial for diagnosing diseases effectively.
A capsule-based device with a biodegradable coating and a sampling hydrogel that absorbs and stores fluid samples from the GI tract, allowing for passive sampling and targeting specific regions by dissolving the coating at specific pH levels, enabling sampling in both the small intestine and colon.
The device allows for non-invasive, accurate, and targeted sampling of microbial communities and biomarkers across the GI tract, including the colon, improving disease diagnosis and patient comfort by avoiding invasive procedures.
Smart Images

Figure 2025509638000001_ABST
Abstract
Description
[Technical field]
[0001] The disclosed embodiments relate to capsules for gastrointestinal sampling and related methods of use. [Background technology]
[0002] The development of new tools that can accurately sample microbial communities, proteins, chemicals, and other biomarkers of interest throughout the gastrointestinal (GI) tract may facilitate more effective and accurate prediction and diagnosis of disease and disease progression.
[0003] Many studies have found that the gut microbiota plays a key role in the pathophysiology governing human health. Many of these studies have identified the impact of the gut microbiota on human metabolism, nutritional intake, the efficacy of orally administered therapeutics, and immune and nervous system function. For example, several studies have found correlations between microbiota imbalance (dysbiosis) and various diseases, including diabetes, obesity, and metabolic syndrome, diseases that affect approximately 30 million people in the United States. Similarly, recent insights into the ways in which gut bacteria may affect the development and maintenance of the nervous system suggest links between gut microbiome composition and the regulation of neuropsychiatric disorders, including dysbiosis in anxiety, depression, and autism.
[0004] Furthermore, many diseases are associated with the production of different biomarkers and mRNA transcripts in the GI tract. For example, fecal calprotectin (fCal) has been shown to be the most accurate in detecting Inflammatory Bowel Disease (IBD) and mucosal damage. Although several studies have demonstrated a link between fCal levels and the degree of inflammation, the level of calprotectin is highly dependent on several factors, including diet, water content in fecal samples, and disease location. Patients with ileal Crohn's Disease (CD) may have large ulcers with low levels of fCal. This may suggest that fecal analysis allows for a simplified assessment of potential IBD, but does not indicate possible disease location or condition. Summary of the Invention
[0005] In one embodiment, a device for passive sampling of the gastrointestinal tract comprises a capsule housing defining a cavity, a sampling opening formed within the capsule housing and providing fluid communication between the cavity and an exterior of the capsule housing, and a sampling hydrogel located within the cavity. Upon exposure to a sample fluid, the sampling hydrogel is configured to absorb the sample fluid and expand within the cavity to store the sample fluid for subsequent analysis. The device further comprises a sealing member located within the cavity between the sampling hydrogel and the sampling opening. Expansion of the sampling hydrogel within the cavity presses the sealing member into engagement with the sampling opening to seal the cavity. The device further comprises a biodegradable coating covering the sampling opening. The biodegradable coating comprises a plurality of biodegradable coating layers. Degradation of the plurality of biodegradable coating layers exposes the sampling opening to allow fluid flow into the cavity.
[0006] In another embodiment, a method of manufacturing a device for passive sampling of the gastrointestinal tract includes providing a capsule housing having a cavity and a sampling opening. The sampling opening provides fluid communication between the cavity and an exterior of the capsule housing. The method further includes closing the sampling opening with a biodegradable coating comprising a plurality of biodegradable coating layers. Degradation of the plurality of biodegradable coating layers exposes the sampling opening to allow fluid flow into the cavity.
[0007] In one embodiment, a device for passive sampling of the gastrointestinal tract includes a capsule housing defining a cavity, a sampling opening formed in the capsule housing and providing fluid communication between the cavity and an exterior of the capsule housing, and a sampling hydrogel located within the cavity. Upon exposure to a sample fluid, the sampling hydrogel is configured to absorb the sample fluid and expand within the cavity to store the sample fluid for subsequent analysis. The device further includes a sealing member located within the cavity between the sampling hydrogel and the sampling opening. Expansion of the sampling hydrogel within the cavity presses the sealing member into engagement with the sampling opening to seal the cavity. The device further includes a biodegradable coating disposed within the sampling opening. Degradation of the biodegradable coating exposes the sampling opening to allow fluid flow into the cavity.
[0008] It should be understood that the foregoing concepts, and additional concepts discussed below, may be arranged in any suitable combination, as the disclosure is not limited in this respect. Moreover, other advantages and novel features of the present disclosure will become apparent from the following detailed description of various non-limiting embodiments when considered in conjunction with the accompanying drawings. [Brief description of the drawings]
[0009] The accompanying drawings are not intended to be drawn to scale. In the drawings, each identical or nearly identical component illustrated in various figures may be represented by a similar numeral. For purposes of clarity, not every component may be labeled in every figure. [Figure 1] FIG. 1 is a schematic diagram showing a capsule moving through the GI tract, according to some embodiments. [Figure 2A] 1 depicts one embodiment of a capsule in a first location within the GI tract. [Figure 2B] 2B depicts the capsule of FIG. 2A at a second location within the GI tract. [Figure 2C] 2A depicts the capsule in a third location within the GI tract. [Figure 2D] 2A depicts the capsule of FIG. 2A at a fourth location within the GI tract. [Diagram 3] FIG. 2 is a partially exploded view of a capsule according to some embodiments. [Figure 4A] FIG. 2 is a schematic diagram showing a first step of a method for producing a coating for a capsule according to some embodiments using a drop casting technique. [Figure 4B] FIG. 4B is a schematic diagram showing a second step of the method of FIG. 4A. [Figure 4C] FIG. 4B is a schematic diagram showing a third step of the method of FIG. 4A. [Figure 4D] FIG. 4B is a schematic diagram showing a fourth step of the method of FIG. 4A. [Figure 4E] FIG. 4B is a schematic diagram showing a fifth step of the method of FIG. 4A. [Diagram 5] 1 depicts an alternative embodiment of a capsule. [Figure 6A] 1 is a plot showing the dissolution profile of Eudragit L100-55 at various pH levels. [Figure 6B] 1 is a plot showing the dissolution profile of Eudragit L100 at various pH levels. [Figure 6C]1 is a plot showing the dissolution profile of Eudragit S100 at various pH levels. [Figure 6D] 1 is a bar graph showing the percentage dissolution of biodegradable coating polymers after two hours of exposure to various pH levels. [Figure 7A] 1 is a plot showing the dissolution profile of Eudragit EPO at various pH levels. [Figure 7B] 1 is a plot showing the dissolution profile of chitosan at various pH levels. [Figure 7C] 1 is a bar graph showing the percentage dissolution of biodegradable coating polymers after 1 hour exposure to various pH levels. [Figure 8] 1 is a bar graph showing the cytotoxicity of biodegradable coatings before and after NIR drying. [Figure 9A] 1 is a plot showing spectroscopy results for enteric polymers in powder form. [Figure 9B] 1 is a plot showing spectroscopy results for enteric polymer films. [Figure 10A] 1 is a plot showing thermogravimetric analysis of various forms of Eudragit L100-55. [Figure 10B] 1 is a plot showing the thermogravimetric analysis of various forms of Eudragit EPO. [Figure 11A] 1 is a microscopic image of a dual-layer biodegradable coating allowed to dry in ambient conditions. [Figure 11B] 11B is a microscopic image of the bilayer biodegradable coating of FIG. 11A after exposure to a pH of 1.2 for 2 hours. [Figure 11C] FIG. 11C is a microscopic image of the bilayer biodegradable coating of FIG. 11B after 6 hours of exposure to a pH of 6.8. [Figure 11D] FIG. 11D is a microscopic image of the bilayer biodegradable coating of FIG. 11C after exposure to a pH of 5.5 for 1 hour. [Figure 11E] 1 is a microscopy image of a bilayer biodegradable coating dried using NIR. [Figure 11F]FIG. 11C is a microscopic image of the bilayer biodegradable coating of FIG. 11E after exposure to a pH of 1.2 for 2 hours. [Figure 11G] FIG. 11F is a microscopic image of the bilayer biodegradable coating of FIG. 11F after 6 hours of exposure to a pH of 6.8. [Figure 11H] FIG. 11C is a microscopic image of the bilayer biodegradable coating of FIG. 11G after 1 hour of exposure to a pH of 5.5. [Figure 12A] 1 is an SEM image of a dual-layer biodegradable coating allowed to dry in ambient environment. [Figure 12B] 1 is an SEM image of a bilayer biodegradable coating dried using NIR. [Figure 13A] 1 is a bar graph showing the GI tract microbiota composition and comparison with the capsule administered to the first animal. [Figure 13B] 1 is a bar graph showing the GI tract microbiota composition and comparison with the capsule administered to a second animal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] At least some embodiments described herein are directed to targeted sampling of microbial communities, proteins, chemicals, and other biomarkers throughout the GI tract.
[0011] Human microbiome sampling has become an essential aspect of understanding the mechanisms of microbiota-drug interactions and the extent to which this complex interaction may affect drug efficacy and bioavailability. Much of what is known about the structure and function of the human gut microbiome has been confirmed from ex situ culture and / or sequencing of bacteria from fecal samples. However, since only a small fraction of gut bacteria is available and culturable from fecal samples, efforts have been made to develop tools that would allow for direct sampling of microorganisms from the gastrointestinal (GI) tract. For example, colonoscopy and / or gastroscopy methods are currently used, but these methods are limited to sampling at specific segments throughout the GI tract, invasive approaches that may cause patient discomfort and lead to reduced compliance. Other approaches have used smart function capsules with the ability to collect samples at various target locations in the GI tract, but these methods may address some of the limitations associated with traditional colonoscopy and gastroscopy. Furthermore, capsule-based devices may improve patient comfort without the need to be administered in a clinical setting. For example, PillCam™ capsule endoscopy (CE) technology is used to collect images from hard-to-reach areas throughout the digestive tract to diagnose diseases associated with the small intestine, such as obscure digestive bleeding, tumors, Crohn's disease, angiodysplasia, celiac disease, and polyposis, but this technology does not have the ability to collect and store samples as they pass through the digestive tract.
[0012] Efforts to develop new capsules with different methods for sampling the gut microbiome can be divided into two main categories: active and passive devices. In active devices, the actuation and sampling mechanism is often achieved by using an on-board battery that provides the energy required to actuate the various plungers, pistons, biopsy forceps, etc. that collect and store the sample within the capsule. However, in such devices, the battery often occupies a large portion of the capsule's volume, which can limit the space in which the sample can be stored, and active devices usually have a high risk of failure and possible leakage of corrosive electrolytes that can cause severe corrosive injury and liquefaction necrosis. To avoid these and other drawbacks associated with active devices, various passive actuation sampling mechanism approaches have been utilized, thereby allowing the capsule to be more compact and economically viable while having fewer safety-related issues. In such designs, the capsule moves through the GI tract via peristaltic motion at an average speed of 1-2 cm / min, and the sample is collected by simple sample passive actuation, e.g., capillary wicking action or pressure differential force. However, the inventors have recognized and appreciated that there are many important design considerations that are not yet addressed by existing passive devices. For example, some existing approaches rely on the assembly of a capsule that requires a well-sealed vacuum chamber within the capsule, which significantly increases the complexity of the device. Other approaches have relied on retrieval of the sampling device via a string that extends upstream of the digestive tract, which can cause discomfort to the patient.
[0013] In some embodiments, a capsule is provided with an opening that forms an opening from the exterior to the interior of the capsule. The opening can be covered with a pH-sensitive enteric polymer coating that dissolves when it enters the basic environment of the small intestine. In some embodiments, there is a hydrogel in the capsule that draws the fluid sample into the capsule. When fluid enters the capsule, the hydrogel swells. An elastomeric disk can be provided with the hydrogel. When the hydrogel swells, the elastomeric disk can be pressed against the opening to seal the capsule from the inside, thereby preventing any further fluid exchange.
[0014] The inventors recognize that in some cases, disposing a biodegradable coating on the exterior of the capsule to cover the opening may require the capsule to have a corner or collar near the opening to contain the liquid solution during application.
[0015] Thus, the inventors have realized that in some embodiments, it may be beneficial to dispose the biodegradable coating within the opening rather than on the exterior of the capsule. Disposing the biodegradable coating within the opening may allow the exterior of the capsule to assume a wider range of geometries, including smoother, more rounded geometries that may be better suited to passing through the GI tract. For example, the capsule may be an elongated oval shape with only a small opening formed at one end. The biodegradable coating may be disposed only within the opening, which allows the exterior of the capsule to have only rounded features. Alternatively or additionally, disposing the biodegradable coating within the opening may increase ease of manufacture. For example, in some embodiments, it may be easier to create a coating layer by depositing a coating material within the containment volume of the opening than by applying the coating material around the exterior surface of a round capsule. In some embodiments, depositing the coating material within the containment volume of the opening may facilitate control of the coating layer thickness. This may be particularly beneficial when multiple coating layers are applied, as discussed below.
[0016] Another limitation of current designs is that they target only the small intestine. The biodegradable coating must resist degradation in an acidic environment to survive in the stomach, but dissolve in a basic environment to allow sampling in the basic environment of the small intestine. Because the large intestine is more acidic, no single pH-sensitive coating has been identified that can withstand both the acidic environment of the stomach and the basic environment of the small intestine to reach the colon intact and dissolve in the colon. This limitation of enteric polymer coating materials has hindered the development of a similar passive sampling device for the colon. As mentioned above, currently available techniques for colon sampling are generally invasive, expensive, time-consuming, and require skilled technicians. Thus, there remains an unmet need for targeted passive sampling from the colon that is convenient for the user.
[0017] The inventors have recognized that in some embodiments, it may be beneficial to include multiple layers of biodegradable coating, each layer dissolving at a different pH level. Such an arrangement may allow the capsule to target different regions of the body for passive sampling. For example, to target passive sampling from the colon, the outer layer may dissolve in a basic environment and the inner layer may dissolve in an acidic environment. The outer layer may survive through the stomach and protect the inner layer from the acidic environment in the stomach. The outer layer may dissolve in the basic environment of the small intestine, thereby exposing the inner layer. The inner layer may survive in the small intestine and dissolve in the acidic environment of the colon, thereby allowing the passive sampling process to occur in the colon.
[0018] The inventors recognize that in some embodiments, it may be useful to use a drop casting process to form one or more of the biodegradable coatings. The inventors recognize that drop casting may be used to generate thick layers within a shorter period of time while maintaining control and simplicity in the application process. For example, an enteric polymer may be dissolved in a liquid solvent to form a polymer solution. Droplets of the polymer solution with a controlled or known size may be deposited on a surface or into an opening with a controlled momentum, and a coating layer with a known thickness is rapidly created. However, it is understood that in other embodiments, other methods for forming the biodegradable coating may be used.
[0019] The inventors also recognize that in some cases, when the solvent used to make the polymer solution is toxic or otherwise not biocompatible, the biocompatibility of the coating may be compromised if the solvent becomes trapped within the polymer matrix. Additionally, the solvent may act as a plasticizer within the polymer matrix, thereby potentially reducing the stiffness of the coating layer and potentially increasing the likelihood of premature failure of the seal. Thus, the inventors recognize that in some embodiments, it may be desirable to remove the solvent from the coating layer after deposition.
[0020] The inventors have recognized that in some embodiments, it may be useful to use Near Infrared (NIR) spectroscopy to dry the polymer solution and remove the solvent after deposition. In the NIR process, waves of known and controlled wavelengths are emitted in the sample material. While NIR is traditionally used as a method to identify unknown materials, the ability to control the emitted wavelength allows wavelengths to be selected that may have higher absorbance in the solvent than in the enteric polymer. Higher absorbance in the solvent may result in evaporation of the solvent, and lower absorbance in the enteric polymer may result in the polymer film structure suffering little or no damage. For example, the NIR process may allow the solvent to evaporate from the polymer matrix in a relatively short time, thereby allowing the solvent to be removed before the polymer matrix is damaged. However, it should be understood that in other embodiments, other methods for removing the solvent may be used, for example, heat is used.
[0021] Additionally, in designs with multiple layers of biodegradable coatings, the ability of each layer to dissolve at the desired point in the GI tract may depend on the separation or stratification of the different biodegradable coatings into separate layers. When different biodegradable coatings are mixed together, the effect is similar to creating a single layer with a concentration gradient throughout. The result is that the overall coating may partially dissolve in each part of the GI tract, potentially compromising the ability of the capsule to specifically target a particular point in the GI tract (e.g., the colon). To prevent mixing, drying or curing of each layer of coating may be performed after deposition and before any subsequent layers are deposited.
[0022] In view of the above, the inventors recognize that in some embodiments, it may be beneficial to apply NIR to a coating layer before applying a subsequent layer.For example, NIR can be used to rapidly dry and remove solvent from a first polymer coating layer after the first polymer coating layer is drop-cast into the opening of the sampling capsule and before drop-casting a second polymer coating layer onto the first layer.Then, NIR can be used to rapidly dry and remove solvent from the second layer, resulting in a biocompatible coating with multiple distinct layers that are structurally intact.However, it should be understood that in other embodiments, other methods for achieving solidification can be used, for example, heat is used.
[0023] In some embodiments, a passive sampling device may include a capsule that may be ingested by a patient and thereby travel through the GI tract. The capsule may include a capsule housing that defines a cavity and an absorbent sampling hydrogel located within the cavity. The capsule housing may include a sampling opening that allows fluid from the GI tract (e.g., fluid containing microorganisms or proteins such as calprotectin) to flow into the cavity where it is absorbed by the sampling hydrogel. Upon absorbing the fluid, the sampling hydrogel may expand within the cavity and press a sealing member (e.g., a sealing membrane) located in the cavity between the opening and the hydrogel material to engage the opening and seal the opening, thereby restricting subsequent fluid from entering or leaving the capsule. In this manner, the devices disclosed herein may utilize the sampling hydrogel as a medium for storing the microbial sample within the capsule and as a means for providing a passive mechanical actuation to seal the capsule once sampling is complete. Additionally, the inventors have realized that after the capsule is sealed, the hydrated sampling hydrogel within the capsule may provide an ideal living environment with nutrients for the sampled bacteria to survive prior to retrieving the capsule. Additionally, according to some embodiments, sealing the capsule can help protect the sample collected within the capsule from the harsh environment located within the digestive tract, thereby preserving the bacterial sample stored within the sampling hydrogel sample for subsequent analysis.
[0024] In some embodiments, the capsule may include a biodegradable coating, the biodegradable coating comprising a plurality of biodegradable coating layers disposed within the sampling opening. For example, the biodegradable coating may be an enteric coating configured to dissolve at a desired target location along the length of the GI tract. In one embodiment, an outer biodegradable coating layer and an inner biodegradable coating layer are disposed within the sampling opening. Thus, the outer biodegradable coating layer may dissolve when the capsule reaches a position prior to the target location (referred to herein as a priming position), and the inner biodegradable coating layer may dissolve when the capsule reaches the target location. Dissolution of the inner biodegradable coating may allow intestinal fluids to enter the capsule cavity through the opening. In some embodiments, the biodegradable coating may be disposed only within the sampling opening, such that the biodegradable coating is constrained within the sampling opening (does not extend to the outer surface of the capsule). It should be understood that the capsule according to the present disclosure may include any suitable biodegradable coating, as would be understood by one of ordinary skill in the art. For example, suitable coating materials include, but are not limited to, pH-sensitive polymeric materials such as basic butylated methacrylate (EUDRAGIT EPO), polymethacrylic acid-co-ethyl acrylate (EUDRAGIT L 100-55), polymethacrylic acid-co-methyl methacrylate (EUDRAGIT L100), hydroxypropyl methylcellulose phthalate (HP-55), hypromellose phthalate (HPMCP), cellulose acetate phthalate (CAP), and polyvinyl acetate phthalate (PVAP).
[0025] In some embodiments, the biodegradable coating is formed using a solution casting technique. In such a technique, a polymer is dissolved in a solution, and the solution is coated onto the cap. In some embodiments, the cap of the sampling capsule is placed on a silicone (e.g., PDMS) holder, which blocks the opening of the cap while the biodegradable coating is deposited on the cap to prevent the biodegradable coating from passing through the opening. The solution may have a high viscosity and may dry quickly. After the coating is dry, the cap may be lifted off the holder. The solution may easily separate from the silicone holder, thus allowing the coating to remain with the cap and cover the opening of the cap. In some embodiments, as described below, the coating may be formed by drop casting, which involves dropping large droplets of controlled size and momentum, which spread over the surface upon impact and wet the surface. In some embodiments, a doctor blade may be used to create a film of uniform thickness. Doctor blading, also known as knife coating or blade coating, involves moving a blade over a surface (or moving the surface under the blade). The small gap between the blade and the substrate determines how much solution can pass through as the blade passes, spreading the solution evenly across the substrate.
[0026] In some embodiments, each layer of the biodegradable coating is formed using a drop casting technique. In such a technique, a biodegradable coating polymer is dissolved in a solution, and the resulting solution is deposited in the sampling opening of the capsule. In some embodiments, the cap of the sampling capsule is placed on a silicone (e.g., PDMS) holder, which blocks the opening while a first solution containing a first biodegradable coating polymer is deposited in the opening to prevent the first solution from passing through the opening. Droplets of the first solution having a known size can be deposited in the opening with a controlled momentum to form a first coating layer having a first thickness. In some embodiments, a second solution containing a second biodegradable coating polymer is deposited in the opening. Droplets of the second solution having a known size can be deposited in the opening with a controlled momentum to form a second coating layer having a second thickness.
[0027] In some embodiments, a doctor blade can be used to create a film of uniform thickness. Doctor blading, also known as knife coating or blade coating, involves moving a blade over a surface (or moving a surface underneath the blade). A small gap between the blade and the substrate determines how much solution can pass through as the blade passes, spreading the solution evenly across the substrate.
[0028] The thickness of the first and second layers may be the same or different. The combined thickness of the overall coating may be selected to be sufficient to prevent premature failure of the coating. Selective variation in the thickness of each layer may allow targeted sampling at specific points along the GI tract. For example, a thicker layer of the second coating may cause the second coating to require more time to dissolve (i.e., a longer dissolution time). The layers may be designed to target segments of the colon for sampling by selecting a thickness for the second coating that results in a dissolution time that corresponds to the transit time through the target segment.
[0029] After the coating has dried, the cap can be lifted off the holder. The coating can easily separate from the silicone holder, thus allowing the coating to remain intact in the opening of the cap. In some embodiments, NIR can be used to accelerate and improve the drying process. During the NIR process, a wavelength can be selected for emission with higher absorbance in the solvent than in the polymer to facilitate removal of the solvent and drying of the solution. In some embodiments, NIR can be used multiple times during the drop casting process. For example, NIR can be used a first time to dry the first solution before depositing the second solution, and a second time to dry the second solution.
[0030] As described above, the capsule may include a sealing member that may be pressed by the sampling hydrogel to engage the sampling opening of the capsule after the sampling hydrogel absorbs the intestinal fluid sample and expands within the capsule cavity. According to some aspects, the sealing member may be configured to provide a desired gas permeability between the capsule cavity and the external environment. For example, in some embodiments, the sealing member may be formed as a polydimethylsiloxane (PDMS) membrane, which may provide a gas permeability that allows natural gas exchange between the digestive tract and the interior (i.e., cavity) of the capsule, which may help maintain the natural metabolism of the sampled bacteria and promote their survival after the capsule is sealed. Other materials suitable for the sealing member include, but are not limited to, polyvinyl chloride (PVC), thermoplastic polyurethane (TPU), silyl olefin copolymer (COC), and perfluoropolyether (PFPE).
[0031] Depending on the particular embodiment, the capsules described herein may be capable of maintaining viable bacteria viable for extended periods of time after the capsule is sealed via a sealing member for subsequent analysis. For example, in some embodiments, the sampling hydrogel and / or sealing member may be constructed and arranged to maintain viable bacteria (i.e., keep viable bacteria alive) in the sample fluid for at least 1 hour, at least 5 hours, at least 10 hours, at least 20 hours, or at least up to 24 hours or more before the sampling fluid is withdrawn for analysis.
[0032] In some embodiments, the device may be used to collect proteins or other biomarkers to investigate conditions in the body. For example, in some embodiments, the device may be used to collect calprotectin in the digestive tract to diagnose inflammatory bowel disease (IBD). Calprotectin is a protein released by neutrophils when there is inflammation in the digestive tract.
[0033] After passing through the digestive tract, the sealed capsule may be excreted by the patient and then retrieved for analysis of the gut microbiome sample contained therein. According to some aspects, the capsule may be constructed and arranged to allow easy disassembly after retrieval, thereby allowing easy retrieval of the sampling hydrogel containing the sample. For example, in some embodiments, the capsule housing may be formed from two or more housing parts that may be removably fastened to each other to allow access to the capsule cavity. In one exemplary embodiment, the capsule housing may be formed from two capsule parts that attach to each other via a threaded mating surface, which may allow easy disassembly of the capsule after retrieval by excretion so that the sampling hydrogel in the capsule may be removed for future culturing and analysis of the bacterial sample contained in the capsule. Other suitable mating surfaces include, but are not limited to, snap-fit mating surfaces, and friction or interference fit mating surfaces.
[0034] According to some aspects, before assembling the various components of the capsule housing, the components may be treated to provide a hydrophilic coating on the capsule housing. The inventors have recognized and appreciated that such treatment may help to facilitate the flow of sample fluid through the sampling opening and into the interior of the cavity where the sampling fluid may be absorbed by the hydrogel material contained therein. In particular, a hydrophilic coating on the surface of the capsule housing may help provide a continuous drawing of fluid from the intestine into the narrow sampling opening of the capsule. Additionally, a hydrophilic coating on the interior surface of the sampling opening may aid in the adhesion of the biodegradable coating to the sampling opening in addition to further contributing to the drawing of fluid from the intestine. For example, in some embodiments, the hydrophilic surface modification may be performed by activating the surfaces of the housing components using air plasma treatment followed by immersion in a Polyethylene Glycol (PEG) solution.
[0035] The hydrogel materials disclosed herein may be composed of hydrophilic polymer networks capable of absorbing large amounts of water while maintaining their structure. These polymer networks are typically crosslinked via covalent bonds, hydrogen bonds, van der Waals interactions, and / or physical entanglements. The devices disclosed herein utilize both the absorptive capacity as well as the mechanical properties of hydrogels to provide a non-invasive sampling device capable of passively extracting and securing samples from target locations along the gastrointestinal tract.
[0036] In some embodiments, the sampling hydrogel in the capsule may be synthesized from a combination of acrylic acid (AA) and acrylamide (AM) monomers. It should be understood that the present disclosure is not limited to a particular ratio of these monomers to form a hydrogel material. For example, suitable ratios of these monomers may include, but are not limited to, 10% AA / 90% AM, 30% AA / 70% AM, 50% AA / 50% AM, 70% AA / 30% AM, or 90% AA / 10% AM. As discussed in more detail below, the hydrogel material may be formed by mixing these monomers with deionized (DI) water and methylene bis-acrylamide (MBA) as a crosslinker and ammonium persulfate (AP) as an initiator. Although certain hydrogel materials are described herein, it should be understood that other hydrogel materials may be suitable, such as hydrogels based on other acrylic polymers (e.g., acrylic acid, acrylamide, poly(N-isopropylacrylamide), poly(N-isopropylacrylamide), and / or N,N-diethylacrylamide) and / or combinations of non-acrylic polymers. In some embodiments, the hydrogel may be synthesized from a combination of acrylamide and N,N'-methylenebisacrylamide (MBA).
[0037] It should be understood that the capsule housing according to the present disclosure may be made from any suitable biocompatible material. For example, in some embodiments, the capsule housing may be formed from a biocompatible polymeric material, such as a methacrylate polymer. Other suitable materials include, but are not limited to, commercially available biocompatible polymers such as Dental LT Clear, MED625FLX, and MED610, and / or other polymeric materials treated with PEG to provide biocompatibility. Furthermore, it should be understood that the present disclosure is not limited to a particular method for forming the capsule housing. For example, some embodiments described in more detail below utilize a capsule housing formed by a 3D printing process. Other suitable manufacturing methods may include, but are not limited to, casting methods, molding methods (e.g., injection molding), or other methods that would be understood by one of ordinary skill in the art.
[0038] Depending on the particular embodiment, the capsule may have any suitable dimensions. For example, a cylindrical capsule may have a length of about 9 mm to about 23 mm and a diameter of about 4.5 mm to about 10 mm. For example, in one embodiment, the capsule may have a diameter of about 9 mm and a length of about 15 mm, which is smaller than a standard 000 size gelatin capsule (having dimensions of 9.97 x 26.14 mm). Additionally, the sampling opening formed in the capsule housing may have a diameter selected based on the size of the sealing member contained within the capsule. For example, in some embodiments, the diameter of the sampling opening may be selected to be at least 1 mm smaller than the diameter of the sealing member, which may help ensure proper sealing of the capsule by the sealing member. In one exemplary embodiment, the sampling opening may have a diameter of about 5 mm.
[0039] With reference to the drawings, certain non-limiting embodiments are described in further detail. It should be understood that the disclosure is not limited to only the specific embodiments described herein, and that the various systems, components, features, and methods described with respect to these embodiments can be used individually and / or in any desired combination.
[0040] FIG. 1 is a schematic diagram of a sampling capsule 102 at various positions 10, 20, 30, 40 in a GI tract 100. FIG. 2A, FIG. 2B, FIG. 2C, and FIG. 2D are schematic diagrams of the sampling capsule 102 in various operating states that may correspond to positions 10, 20, 30, 40 in FIG. 1, respectively. As shown in FIG. 2A, the capsule 102 includes a biodegradable coating 106 (e.g., an enteric coating), which has an outer biodegradable coating layer 108 and an inner biodegradable coating layer 110. The biodegradable coating 106 is disposed within a sampling opening 112 of the capsule 102, such that the biodegradable coating 106 seals the sampling opening 112. In this manner, the biodegradable coating 106 protects components within the capsule cavity 104, including the sampling hydrogel 114 and the sealing member 116, and delays sampling until the capsule reaches a target location in the GI tract. In some embodiments, the biodegradable coating 106 may be disposed only within the sampling opening and not on the exterior surface of the capsule. As shown in FIG. 2B, when the capsule reaches a priming location in the GI tract (which may be a point in the GI tract prior to the target location), the outer biodegradable coating layer 108 degrades, exposing the inner biodegradable coating layer 110 to the GI fluid surrounding the capsule. As shown in FIG. 2C, when the capsule 102 reaches the target location, the inner biodegradable coating layer 110 degrades, allowing GI fluid containing the sample material 118 (e.g., bacteria, proteins, chemicals, and / or potentially other compounds of interest) to enter the capsule, where the fluid is absorbed by the sampling hydrogel 114. Upon absorbing the fluid, the sampling hydrogel expands and swells within the cavity 104, filling substantially the entire volume of the cavity. Additionally, as shown in Figure 2D, the expansion of the sampling hydrogel presses the sealing member 116 into contact with the sampling opening, thereby sealing the sampling opening via the mechanical force applied by the swollen hydrogel. As shown, the fluid absorbed by the sampling hydrogel may contain sample material 118 from within the GI tract.After the capsule has been excreted, it may be disassembled to allow recovery of the sampling hydrogel and the bacterial sample contained therein so that the bacteria can be subjected to future culture and analysis.
[0041] When a patient swallows an exemplary embodiment of a sampling device having two layers of biodegradable polymer coating, the device may be exposed to saliva at a pH of 7, typically for less than one minute. As the device moves toward the stomach, the pH drops to about 3. The device may still be inert since the outer enteric polymer is still non-ionized in the acidic pH environment of the stomach. As the device moves further down the digestive tract, the pH increases, and when the device reaches the small intestine, the average pH is 6.8, typically with a maximum pH of 7.5. When the pH exceeds the dissolution threshold of the outer biodegradable coating layer, the outer polymer begins to ionize, initiating polymer dissolution. When the outer biodegradable coating layer dissolves, the inner biodegradable coating layer is exposed to the fluids of the small intestine. At this point, the device may still be inert since the inner biodegradable coating layer is still non-ionized in the basic pH environment of the small intestine. When the device reaches the ascending colon where the pH suddenly drops again, the inner biodegradable coating layer may begin to ionize and dissolve in the acidic environment of the colon. As the inner biodegradable coating layer dissolves, intestinal fluids may enter the cavity 104 and the hydrogel may begin to swell by absorbing the intestinal fluids while pushing the sealing member in the cavity towards the sampling opening. With the device opening sealed with the sealing member, the device may travel through the remainder of the GI tract without fluid exchange.
[0042] In some cases, it may take approximately 24-72 hours for the device to travel through the colon. Depending on the intended use of the device, biodegradable coating dissolution and / or hydrogel elongation may be tailored to a desired target location within the small intestine. Biodegradable coating dissolution may be tailored by selecting an appropriate thickness for one or more coating layers described above. For example, in some embodiments, the biodegradable coating may be configured to target the ascending colon by selecting a coating thickness for the inner biodegradable coating layer to provide complete dissolution within 2 hours after the device enters the colon. The hydrogel may then be configured to elongate within 1 hour, and the device may finally be configured to be sealed by a sealing member within 0.5 hours. In an example targeting the transverse colon, the biodegradable coating may be configured to target the ascending colon by selecting a coating thickness for the inner biodegradable coating layer to provide complete dissolution within 11 hours after the device enters the colon. The hydrogel may then be configured to stretch within 1 hour, and the device may finally be configured to be sealed by the sealing member within 0.5 hours. These time target intervals may be selected to allow a desired length of time for a safety margin to ensure that the device is sealed prior to evacuation. After evacuation, the capsule may be collected and disassembled, and samples may be analyzed for further investigation.
[0043] 3 is a schematic exploded view of one embodiment of a capsule 202 for passive sampling of the GI tract. The capsule 202 includes a capsule housing 220, which includes a first housing portion 222 (also referred to herein as a cap) and a second housing portion 224. The first housing portion includes a sampling opening 212 for providing fluid communication between the exterior of the capsule and a cavity 204 formed in the capsule housing 220. A biodegradable coating 206, including an outer biodegradable coating layer 208 and an inner biodegradable coating layer 210, is provided within the sampling opening 212 to seal the sampling opening 212 until the capsule 202 reaches a desired location within the GI tract. In some embodiments, the biodegradable coating may be disposed only within the sampling opening, such that the biodegradable coating 206 is constrained within the sampling opening (does not extend to the exterior surface of the capsule). The sampling hydrogel 214 and the sealing member 216 are located within the cavity 204, and as shown, the sealing member 216 is located between the sampling hydrogel 214 and the sampling opening 212. As noted above, in some embodiments, the sealing member 216 may be a flexible membrane, such as a PDMS membrane, that may provide gas permeability between the cavity 204 and the exterior of the capsule 202 after the sealing member seals the cavity. Additionally, the first and second housing portions 222 and 224 include an attachment interface 226 to allow the capsule housing to be easily disassembled and the hydrogel material retrieved after the sample has been collected. In the depicted embodiment, the attachment interface 226 comprises corresponding threaded features formed on the first and second housing portions, which cooperate to form a threaded interface. However, as noted above, other attachment arrangements, such as a snap fit or an interference fit, may be suitable in other embodiments.
[0044] In the depicted embodiment, the sampling opening has a circular shape. However, it should be understood that the sampling opening 212 may have any suitable shape. The shape of the sampling opening 212 may determine the shape of the biodegradable coating 206 disposed within the sampling opening 212. For example, in some embodiments, the sampling opening may be square, rectangular, oval, or any other suitable shape.
[0045] 4A-4F show schematic diagrams of one embodiment of a method for producing a capsule having multiple layers of a biodegradable coating disposed within the sampling opening of the capsule. In FIG. 4A, the first housing portion 322 of the capsule is placed on a fixture 330 in the direction of the arrow shown. The fixture 330 has a sealing plate 332 configured to provide a liquid-tight seal with the first housing portion 322 of the capsule around the sampling opening 318 of the capsule. The sealing plate 332 can be a silicone material (e.g., PDMS) or any other material that provides a liquid-tight seal without bonding or adhering to the biodegradable coating. A liquid solution of the first biodegradable coating 308 is introduced into the opening 318. As shown in FIG. 4C, the liquid-tight seal between the sealing plate 332 and the first housing portion 322 of the capsule can hold the first biodegradable coating 308 within the opening. The first biodegradable coating 308 is then dried. In some embodiments, drying may include the use of NIR, as represented by arrow 334 in Figure 4C. As discussed below, any suitable parameters for the use of NIR may be appropriately selected, including wavelength, operating power, and scan speed.
[0046] In some embodiments, the wavelengths used in the NIR drying process may be 300 mm, 400 nm, 500 mm or more, and / or any other suitable wavelength. In some embodiments, the wavelengths may be 2.0 μm, 2.25 μm, 2.5 μm or less, and / or any other suitable wavelength. Combinations of the above are contemplated, including, for example, 300 mm or more and 2.5 μm or less, 400 mm or more and 2.25 μm or less, and / or any other suitable combination of the above. Of course, while specific ranges for NIR wavelengths are provided above, it should be understood that other ranges, both greater than and less than the above, are also contemplated, as the disclosure is not limited in this manner.
[0047] In some embodiments, the operating power used in the NIR drying process may be 1 kW, 3 kW, 5 kW or more, and / or any other suitable power level. In some embodiments, the operating power may be 8 kW, 10 kW, 15 kW or less, and / or any other suitable power level. Combinations of the above are contemplated, including, for example, 1 kW or more and 15 kW or less, 3 kW or more and 8 kW or less, and / or any other suitable combination of the above. Of course, while specific ranges for NIR operating power are provided above, it should be understood that other ranges, both greater than and less than the above, are also contemplated, as the disclosure is not limited in this manner.
[0048] In some embodiments, the scanning speed used in the NIR drying process may be 1 m / min, 3.6 m / min, 5 m / min or more, and / or any other suitable speed. In some embodiments, the scanning speed may be 7.5 m / min, 10 m / min, 12.5 m / min or less, and / or any other suitable speed. Combinations of the above are contemplated, including, for example, 1 m / min or more and 12.5 m / min or less, 3.6 m / min or more and 7.5 m / min or less, and / or any other suitable combination of the above. Of course, while specific ranges for the NIR scanning speed are provided above, it should be understood that other ranges, both greater than and less than the above, are also contemplated, as the disclosure is not limited in this manner.
[0049] As shown in FIG. 4D, when the first biodegradable coating 308 is dry, a second biodegradable coating 310 may be introduced into the opening 318. The second biodegradable coating 310 is then dried. In some embodiments, the drying may include the use of NIR, as represented by arrow 334 in FIG. 4E. The first housing portion 322 is removed from the fixture, and the sealing plate 332 is separated from the first biodegradable coating 308 without damaging the coating. In some embodiments, the above method may produce a biodegradable coating that is disposed only within the sampling opening, thereby being constrained within the sampling opening (not extending to the exterior surface of the capsule).
[0050] 5 shows a schematic diagram of an alternative embodiment of a capsule 402. The capsule 402 includes a biodegradable coating 406 (e.g., an enteric coating) having an outer biodegradable coating layer 408 and an inner biodegradable coating layer 410. The biodegradable coating 406 is disposed on the outer surface 418 of the capsule 402 and over the sampling opening 412 of the capsule 402, such that the biodegradable coating 406 seals the sampling opening 412. In this manner, the biodegradable coating 406 protects the components within the capsule cavity 404, including the sampling hydrogel 414 and the sealing member 416, and delays sampling until the capsule reaches a target location in the GI tract. When the capsule reaches a priming location in the GI tract (which may be a point in the GI tract prior to the target location), the outer biodegradable coating layer 408 degrades, exposing the inner biodegradable coating layer 410 to the GI fluids surrounding the capsule. When the capsule 402 reaches the target location, the inner biodegradable coating layer 410 degrades, allowing bacteria-containing GI fluid to enter the capsule, where the fluid is absorbed by the sampling hydrogel 414. Upon absorbing the fluid, the sampling hydrogel swells and expands within the cavity 404, filling substantially the entire volume of the cavity. Additionally, the expansion of the sampling hydrogel presses the sealing member 416 into contact with the sampling opening, thereby sealing the sampling opening through the mechanical force applied by the swollen hydrogel. The fluid absorbed by the sampling hydrogel may contain bacteria from within the GI tract. After the capsule is voided, it may be disassembled to allow recovery of the sampling hydrogel and the bacterial sample contained therein, so that the bacteria may be subjected to future culture and analysis.
[0051] In the depicted embodiment, the biodegradable coating 406 initially covers or surrounds only a portion of the capsule 402. However, it should be understood that other arrangements may be suitable, for example, an arrangement in which the biodegradable coating 406 covers or surrounds the entire exterior of the capsule 402. In some embodiments, the biodegradable coating may have a curved exterior surface. In some embodiments, the biodegradable coating may have a flat exterior surface. The biodegradable coating may be of any shape that seals the sampling opening of the capsule. The biodegradable coating of FIG. 5 may be deposited on the capsule by any suitable method, including drop casting, doctor blading, solution casting, or spray coating. It should be noted that any of these methods may be disposed only within the sampling opening, thereby producing a biodegradable coating that is constrained within the sampling opening (and does not extend to the exterior surface of the capsule). EXAMPLES
[0052] Device fabrication In one embodiment, a device for passive sampling of the colon was fabricated using 3D printing. The device consisted of four components: a biodegradable coating including a first and a second biodegradable coating layer, a 3D printed housing including a first housing part and a cap, a sampling hydrogel, and a gas-permeable PDMS membrane. The 3D printed housing was designed in SolidWorks (Dassault Systemes) and printed using stereolithography techniques using a Form 3 3D printer, followed by rinsing with pure isopropyl alcohol (IPA) and UV light curing at 60°C for 15 minutes. The PDMS membrane was fabricated using a standard 1:10 ratio of curing agent to silicone base and cured at 70°C for 4 hours. A circle with a diameter of 6 mm was cut in the PDMS using a computer-controlled CO2 laser cutting and engraving system (PLS6MW from Universal Laser, Inc., operating at a wavelength of 10.6 μm). The hydrogel was synthesized by dissolving acrylamide and MBA crosslinker in water. The solution was then degassed by bubbling nitrogen gas for 10 minutes, and then Ammonium Persulfate (APS) was added to the solution to act as an initiator. Finally, the solution was poured into a mold and polymerized overnight at 70°C. To prevent the device from floating in the fluid, a water-jetted cylindrical copper disk was placed at the bottom of the housing. The copper disk was coated with PDMS to preserve the biocompatibility of the device.
[0053] Characterization of the biodegradable coating layer pH-sensitive polymers include the broad category of polyacids and polybases. Polyacids can attract protons at low pH and release protons at either neutral pH or higher pH. Thus, polyacids, such as Eudragit L100, Eudragit L100-55, and Eudragit S100, can be dissolved in aqueous media at high pH but are insoluble in lower pH ranges. Polybases can attract protons at higher pH and release protons at either neutral pH or lower pH ranges. Thus, polybases, such as chitosan and Eudragit EPO, can be dissolved in aqueous media at low pH but are insoluble in higher pH ranges. The release and attraction of protons of these polyelectrolytes and the resulting solubility or insolubility are controlled by the pH in the surrounding environment.
[0054] To better assess the dissolution of various pH-sensitive polymers, methylene blue and deep orange food coloring dyes were added to solutions of Eudragit L100-55 and Eudragit EPO, respectively. These dyes allowed peak absorbance in the polymer during Ultraviolet Visible (UV-Vis) spectroscopy. The solutions were then cast onto acrylic sheets using doctor blading to obtain uniform film thickness. After casting each layer, the films were then immersed in NIR (Adphos NIR-126-250 Modul, 3.6 m.min) to avoid any solvent entrapment in the film composition. -1 The layers were then completely dried using a conveyor line speed of 100 rpm and lamp power of 3 kW. When the layers were dry, identical disks having a diameter of 10 mm were cut using a computer controlled CO2 laser cutting and engraving system at a wavelength of 10.6 μm.
[0055] Dissolution tests of pH-sensitive polymer samples were performed in 900 mL of various dissolution media at 37° C. using a USP type II apparatus (PTWS instrument, Pharma Test, Hainburg, Germany) with a paddle speed of 100 rpm. The dissolution media had pH values of 1.2, 3, 5.5, 6.8, and 7.4. The polymer samples were removed from the dissolution media at the designated time points and analyzed by UV-Vis using a BMG Clariostar microplate reader (BMG Labtech, Germany), and then placed back into the dissolution media. The percentage of dye released from the formulation was measured using UV-Vis techniques at wavelengths corresponding to the peak wavelength of the appropriate dye. All tests were performed in triplicate.
[0056] The resulting dissolution studies of different polyacids (FIGS. 6A-6D) and polybases (FIGS. 7A-7C) in the GI tract pH environment showed a wide variety of dissolution profiles, suggesting that a range of dissolution kinetics and profiles can be achieved by different formulations.
[0057] As shown in Figures 6A-6C, among the polyacid polymers in the simulated fasted state (pH = 1.2) of the stomach, all three polyacids showed minimal dissolution (less than 10%) during the simulated gastric residence time (2 hours). Continuation of the experiment up to 8 hours of residence time did not result in substantial changes in this trend. Also, as shown in Figures 6A-6C, in the simulated fasted state (pH = 3.0), all three polyacids showed less than 15% dissolution within 2 hours of gastric residence time. However, Eudragit L100-55 showed a slow continuous dissolution trend, which reached about 30% after 8 hours of residence time (Figure 6A).
[0058] At pH=5.5, which generally mimics the pH of both the duodenum and the cecum, Eudragit L100-55 shows approximately 30% dissolution after 2 hours (FIG. 6A). However, Eudragit L100 and Eudragit S100 were still almost insoluble after 8 hours, showing 21% (FIG. 6B) and 11% (FIG. 6C) dissolution, respectively. At pH=6.8, which generally mimics the proximal small intestine region, the threshold pH level for dissolution of Eudragit L100-55 is met. This could cause Eudragit L100-55 to be fully ionized and completely dissolved within 2 hours (FIG. 6A). Complete dissolution of Eudragit L100 occurred after 5 hours (FIG. 6B), while Eudragit S100 was only 20% dissolved after 8 hours (FIG. 6C).
[0059] Dissolution profiles for the polybase polymers Eudragit EPO and chitosan are shown in Figures 7A-7C. Chitosan showed relatively rapid dissolution at all pH levels, with complete dissolution occurring within 5-6 hours at each pH level. Eudragit EPO showed complete dissolution within 1 hour at pH levels of 1.2, 3.0, and 5.5, and within 3 hours at a pH of 6.8. However, at a pH of 7.4, dissolution of Eudragit EPO did not exceed about 30% over the entire 8 hour residence time.
[0060] Near infrared drying In several studies, NIR techniques have been applied to increase the evaporation rate of the solvent and prevent intermixing of the polymer layers while preserving the integrity of the polymer film structure.
[0061] Characterization of reduced cytotoxicity from NIR The in vitro cytotoxicity of samples with bilayer biodegradable coating was determined using human mesenchymal stem cells (hMSCs) by MTT (tetrazolium bromide) assay. Cytotoxicity was investigated both before and after NIR treatment. The cytotoxicity of capsules without biodegradable coating was selected as a control to partially ensure that the cured 3D printed resin was non-toxic to cells. Since the coating included two drop-casted layers, an investigation of the cytotoxicity of the biodegradable coating was performed. An investigation was performed to verify whether the drop-casted layers released organic solvents as potential carcinogens and neurotoxins.
[0062] Cells were cultured in Dulbecco's Modified Eagle Medium (DMEM) with 10% Fetal Bovine Serum (FBS), 100 units / mL penicillin, and 100 units / mL streptomycin. Cells were grown in a humidified incubator at 37°C, 5% CO2, and 95% relative humidity. When cells were confluent (approximately 80%), samples were transferred to 24-well plates and UV sterilized for 2 hours (1 hour per side), and then cells were plated at 2 × 10 per well. 4 Cells were seeded at a density of 1000 μL and a final volume of 2 mL. After 24 h of incubation, the culture medium in each well was replaced with 1800 μL of fresh DMEM and 200 μL of MTT solution (5 mg / mL thiazolyl blue in PBS) and incubated for another hour. The optical density (OD) values of the mixtures were measured at 490 nm using a BMG microplate reader. Cell viability was calculated using the following equation: Percentage cell viability = viable cells on test surface / viable cells on control surface x 100%
[0063] As shown in Figure 8, the cell viability of the control was calculated as 92%, which indicated that the capsule housing was biologically safe. However, the cell viability of the drop-casted film dried in the environment showed a decrease to less than 50% before applying NIR. This toxicity of the bilayer film may be mainly caused by the top layer, because a larger proportion of the solvent may be trapped within the structure of Eudragit L100-55 as a result of the higher molecular weight of the top layer compared to the lower layer, which has a lower molecular weight, which will be discussed in more detail below.
[0064] Cell viability after NIR heat treatment increased to 84%, suggesting that polymer dissolution was harmless to cells. The biocompatibility of the NIR-treated biodegradable coating was attributed to the evaporation of trapped solvent. This is consistent with the Thermogravimetric Analysis (TGA) results discussed below.
[0065] ATR-FTIR characterization of NIR effects To ensure that the bilayer drop-casting films did not show intermixing effects after using NIR treatment, the infrared spectra of single layers of L100-55 and EPO polymers were measured by Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR) using a PerkinElmer Spectrum 100 FTIR spectrometer at 4000 cm -1 ~550cm -1 The infrared spectrum of the bilayer film was compared by scanning 50 times using a range of 100 nm to 100 nm. Single layers of Eudragit L100-55 and Eudragit EPO were evaluated in both film and powder form. Figure 9A shows the comparative ATR-FTIR spectra of pure EPO and L100-55 powders, and Figure 9B shows the comparative ATR-FTIR spectra of pure EPO and L100-55 films and the bilayer coating film.
[0066] As shown in FIG. 9A, the ATR-FTIR spectra for pure L100-55 and EPO powders show a stretching vibration pattern of about 1700 cm, which is assigned to the C═O stretching vibration pattern of the ester group and the C-O bond of the carboxylate ester, respectively. -1 and 1100cm -1 Additionally, the spectrum for Eudragit EPO demonstrated a major characteristic peak at approximately 2850 cm -1 The results showed a stretching band at 100 nm, which may be due to the dimethylamine group that may distinguish L100-55 from EPO.
[0067] As shown in Figure 9B, the ATR-FTIR spectrum of the film showed significant peaks for both L100-55 and EPO without any significant additional vibrational bands for solvent residues. These observations revealed that NIR treatment is a capable drying technique that can remove all the solvent without affecting the polymer film structure.
[0068] Also, as shown in Figure 9B, the ATR-FTIR spectrum for the bilayer coated film demonstrated the characteristic peaks for the pure L100-55 polymer without any prominent peaks indicating intermixing of the EPO layer into the L100-55 film. Since the top coating was a pure L100-55 film, this observation confirms that the expected separation of the two polymer films could have occurred from the immiscible behavior of the initial polymer solutions.
[0069] TGA characterization of NIR effects Thermal characterization of Eudragit L100-55 (shown in FIG. 10A) and Eudragit EPO (FIG. 10B) in both powder and film configurations was carried out using thermogravimetric analysis (TGA). In one film configuration, the film was dried in ambient air. In the other film configuration, the film was dried using NIR. No solvent was used in the powder configuration.
[0070] The difference in weight loss between the powder and film configurations can be attributed to the loss of moisture and solvent present in the film configuration, since these factors are absent in the powder configuration. Additionally, the ambient dried film may have trapped a higher percentage of solvent than the NIR dried film. As shown in both Figures 10A and 10B, NIR drying may have removed a greater percentage of trapped solvent than ambient drying, resulting in a TGA curve that is closer to that of the powder form.
[0071] In all cases of Eudragit L100-55 (Figure 10A), the weight loss between 50 and 150°C can be attributed to the evaporation of excess solvent, and the loss between 225 and 425°C can be attributed to thermal decomposition of the polymer structure. For Eudragit EPO in Figure 10B, the loss between 275 and 325°C can be the result of solvent evaporation, and the larger drop between 375 and 450°C can be due to thermal decomposition.
[0072] NIR shows that the effect on Eudragit L100-55 is significantly greater than Eudragit EPO. This may be due to the higher molecular weight of Eudragit L100-55. Eudragit L100-55, which has a molecular weight of 320,000 g / mol, is much heavier and more viscous than Eudragit EPO, which has a molecular weight of only 47,000 g / mol. This higher molecular weight may cause substantially more entanglement and entrapment of solvent particles, potentially making them more difficult to remove without the aid of drying techniques, such as NIR. As a result, it is observed that the difference between Eudragit L100-55 dried by NIR and Eudragit L100-55 dried in ambient environment is significantly greater than the difference between Eudragit EPO dried by NIR and Eudragit EPO dried in ambient environment. Since radiation from the NIR is not destructive to the polymer structure, the solvent molecules can be targeted for evaporation without affecting the film structure or capsule body.
[0073] Microscopic characterization of NIR effects To visualize the effect of NIR on the morphology and intermixing of the bilayer biodegradable coating, cross-sectional images of the bilayer coating were taken. Because the solvents for both Eudragit L100-55 and Eudragit EPO were essentially the same, there could be a high possibility of polymer intermixing when the layers were allowed to dry slowly under ambient conditions. In some cases, intermixed polymers could result in unintended dissolution profiles at various pH levels. For example, FIG. 11A shows bilayer formation when the top and bottom layers were allowed to dry in an ambient environment. The mixture shown in FIG. 11A confirms that the two polymers are blended with each other. In this configuration, the bilayer coating may not show the intended response to various pH levels. The blending of the layers could occur in part because the slow drying process of the top layer could allow the solvent to dissolve the bottom layer. This effect, where the application of the top layer can cause the bottom layer to dissolve over time, could result in intermixing of the polymers.
[0074] FIG. 11B shows the configuration of FIG. 11A after 2 hours of exposure to a pH level of 1.2. Under these conditions, the top layer could not protect the bottom layer from dissolution as a result of intermingling of the two layers. Thus, the orange layer was completely dissolved and the thickness of the blue layer was significantly reduced. FIG. 11C shows that after 6 hours at a pH of 6.8, the remaining top layer was completely dissolved. This dissolution of the top layer is to be expected due to the pH level exceeding the pH dissolution threshold of the top layer polymer (Eudragit L100-55). FIG. 11D shows that there was no bottom layer left to dissolve at a pH level of 5.5 simply because the bottom layer had already dissolved as a result of intermingling.
[0075] 11E-11H show the effect of NIR treatment on the bilayer coating. Using NIR treatment, blending of the polymers was prevented through rapid and effective drying of the film. As shown in FIG. 11E, the bottom and top layers were more clearly separated and better stratified with individual layers. The layers showed virtually no dissolution or change in thickness after immersion at a pH of 1.2 for 2 hours (FIG. 11F). This may be because the pH did not exceed the dissolution threshold of the top layer of Eudragit L100-55. Thus, the top layer could be preserved and acted as a shield to prevent the bottom layer from being exposed to a lower pH environment that would cause dissolution of the bottom layer. However, as shown in FIG. 11G, when the pH was increased to 6.8, the dissolution threshold of the top layer is met. FIG. 11G shows the complete dissolution of the top layer after 6 hours at a pH level of 6.8. As the top layer dissolved, the bottom layer was exposed to a higher pH environment. As shown in FIG. 11H, the pH was then reduced to 5.5 for 1 hour after which the bottom layer was completely ionized and dissolved.
[0076] SEM characterization of NIR effects Additionally, high magnification cross-sectional images of the bilayer biodegradable coating both before and after NIR treatment are shown in Figures 12A and 12B. These images were taken using a scanning electron microscope (SEM) (Hitachi-S 4800, Tokyo, Japan). As shown in Figure 12A, the top layer (Eudragit L100-55 dried in ambient environment) showed significant porosity. The bottom layer (Eudragit EPO dried in ambient environment) shows significantly less porosity than L100-55. These pores may be formed as a result of the slow drying process in ambient conditions. Additionally, as mentioned above, the higher molecular weight of Eudragit L100-55 may cause a large degree of entanglement between the polymer chains and particles of both solvents and air, which actually prevents the solvent and air particles from easily escaping from the polymer structure.
[0077] FIG. 12B shows that there is no similar porosity issue in the Eudragit L100-55 top layer when the coating layer is dried using NIR. This may be a result of the pulsed heat generated by the lamp energizing the solvent and air particles, thereby forcing the air bubbles to escape from the polymer matrix, ultimately resulting in a pore-free and crack-free polymer structure. Briefly, the microscope and SEM cross-sectional images after NIR processing can demonstrate the efficiency of this technique in not only achieving proper dissolution and protection in different pH environments, but also supporting acceptable polymer morphology.
[0078] Bacterial sampling In vitro studies To evaluate the sampling capabilities of both the hydrogels and the overall device, four vessels containing a mixture of gut microbiota were prepared. Each vessel contained a different mixture, as shown in Table 1 below. The composition of the samples drawn by each device and each hydrogel was compared to the composition of the initial mixture. The bacteria used included Lactobacillus cremoris (Firmicutes), Bacteroides fragilis (Bacteroidetes), Escherichia coli LF82 (Proteobacteria), and Akkermansia muciniphila (Verrucomicrobia), as shown in Table 2. The bacterial strains were cultured overnight at 37° C. in an anaerobic chamber with their respective broths, also shown in Table 2.
[0079] [Table 1]
[0080] [Table 2]
[0081] Separately, the fully assembled device and the free swelling hydrogel were immersed in a container for 2 hours while incubating at 100 rpm at 37° C. The complete device was then disassembled. The disassembled components and the free swelling hydrogel were transferred into separate vials with 4 mL of DI water and extracted on a shaker at 100 rpm for 2 hours.
[0082] After 2 hours of extraction, DNA extraction was performed using the Invitrogen™ PureLink™ Genomic DNA Mini Kit (Invitrogen, USA) in extraction buffer (DI water). Each bacterial mixture was aliquoted before ("pre") and after ("post") sampling with the device or hydrogel. Table 1 shows that all bacterial compositions sampled by the complete device were similar to the corresponding mixtures (both pre and post). Although the results for the hydrogel alone were less representative, this in vitro bacterial sampling experiment confirmed the ability of the capsule device to draw a representative sample of the gut microbiota.
[0083] In vivo studies In vivo evaluation of device function was performed using pigs. The experiment was approved by the Purdue University Animal Care and Use Committee according to protocol number 1911001975A002. Prior to the experiment, pigs were weighed (each weighing approximately 40-50 kg) and housed individually in metabolic crates. The pigs were subjected to a 5-day acclimation period in their new environment and had free access to water. Their diets, based on corn and soybean meal, were formulated to meet or exceed NRC (2012) requirements. The pigs were fed at a daily level of 3 times their estimated energy maintenance requirement (i.e., 197 kcal ME / kg BW; approximately 4% of pig body weight per day) and daily allotments of feed were provided each morning.
[0084] The pigs were fasted for 12 hours before administration of the capsules. Two hours after administration of the capsules, the pigs were fed a diet containing a resistant ferric oxide marker to determine the digestive transit rate. The pigs were then observed at 30-minute intervals to determine the length of time required for the marker to be excreted in the feces (red color).
[0085] The capsules were administered orally using a dosing gun designed for use in pigs. When the capsules were expelled and collected, each pig was euthanized and the pH of various sections in the GI tract was measured. To avoid potential errors in fluid homogenization and pH values, the stomach, small intestine, and large intestine were isolated using cable ties. To achieve more accurate profiling, the small intestine was sectioned in 2 meter increments (Duo: duodenum, J: jejunum, Ile: ileum used in Figure 13A, Figure 13B), and the large intestine was sectioned in 1 meter increments (LI: large intestine used in Figure 13A, Figure 13B). The fluid contents of each section were transferred into disposable plastic weighing boats and pH values were obtained from these fluid contents.
[0086] The administered capsules were collected from the animals after excretion. After wiping and rinsing the external fecal matter, the capsules were disassembled. The disassembled components were transferred into separate vials with 4 mL of sterile DI water and extracted on a shaker at 100 rpm for 2 hours.
[0087] For each of the luminal content samples, DNA was extracted using the QIAamp PowerFecal Pro DNA Kit (Qiagen, Germany) according to the manufacturer's recommendations. The DNA concentration and quality of each sample was measured with a NanoPhotometer NP60 (Implen, Germany).
[0088] For all DNA extraction samples, the V4 region of the 16S rRNA gene was amplified with the PCR primers 515 forward, 5'GTGCCAGCMGCCGCGGTAA, and 806 reverse, 5'GGACTACHVGGGTWTCTAAT. PCR reactions were performed individually in a total volume of 50 μL using Thermo Scientific™ Phusion High-Fidelity PCR Master Mix (Thermo Scientific, USA) according to the manufacturer's recommendations. Verification of the expected amplicon size (approximately 254 bp) was performed by 2% agarose gel electrophoresis. The PCR products were then purified using the Invitrogen™ PureLink™ PCR Cleanup Kit (Invitrogen Life Technologies, USA).
[0089] After checking sample quality using a NanoPhotometer NP60, PCR products were sent to the Purdue Genomics Core Facility for WideSeq (next-generation sequencing) analysis. Sequencing libraries were generated using the Nextera DNA Library Preparation Kit (Illumina, CA, USA), and multiplexed libraries were sequenced using MiSeq (Illumina, CA, USA) to generate paired-end reads (2 × 250 bp). Paired-end reads from each sample were processed to remove adapters and low-quality bases. Only selected paired reads were used for further processing. Reads were then de novo reconstructed into complete sequences and taxonomically assigned using the Silva rRNA database.
[0090] The V4 region of 16S rRNA was amplified and sequenced from 17 different luminal content samples from pig 1 and pig 2. An average of 52,413 total reads per sample were obtained by a MiSeq instrument (Illumina, CA, USA). Sequences were processed to remove adapters and low-quality bases. Sorted reads were de novo reassembled into complete sequences and taxonomically assigned using the Silva rRNA database and clustered into 12 phyla. Results were used to generate microbial taxonomic composition profiles for pig 1 and pig 2.
[0091] The results shown in Figures 13A and 13B showed that the microbiota composition could vary significantly along the porcine intestine, especially between the small and large intestines. The most predominant phylum throughout the intestine was Firmicutes (64%-99%). The phylum Bacteroidetes increased in the large intestine segments, representing 19%-32% of the total bacteria. The difference between the proportion of Bacteroidetes / Firmicutes in the small intestine and the proportion of Bacteroidetes / Firmicutes in the large intestine could be used as a biomarker to indicate the sampling location of the device.
[0092] The two devices administered to pigs 1 and 2 were also collected and analyzed by the same process via WideSeq. Capsule 1 from pig 1 was found in pig 1's feces. Capsule 2 from pig 2 was not excreted by the time of euthanasia and was found in the large intestine sample during dissection of the GI tract. Capsule 1 had a Firmicutes and Bacteroidetes composition of 73% and 24%, respectively. This result was very similar to the large intestine profile of pig 1 (75-78% and 19-21%, respectively). Capsule 2 had a lower Bacteroidetes composition (4%). However, the Bacteroidetes composition was still significantly higher (0.02-0.06%) than the Bacteroidetes composition in the small intestinal segments of pig 2. This indicates that the sampling device drew samples from the large intestine as intended and expected.
[0093] While the present teachings have been described in conjunction with various embodiments and examples, it is not intended that the present teachings be limited to such embodiments or examples. On the contrary, the present teachings encompass various alternatives, modifications, and equivalents, as will be appreciated by those skilled in the art. Accordingly, the foregoing description and drawings are by way of example only.
Claims
1. 1. A device for passive sampling of the gastrointestinal tract, comprising: a capsule housing defining a cavity; a sampling opening formed in the capsule housing and providing fluid communication between the cavity and an exterior of the capsule housing; a sampling hydrogel located within the cavity, the sampling hydrogel configured, upon exposure to a sample fluid, to absorb the sample fluid, to expand within the cavity, and to store the sample fluid for subsequent analysis; a sealing member positioned within the cavity between the sampling hydrogel and the sampling opening, such that expansion of the sampling hydrogel within the cavity urges the sealing member into engagement with the sampling opening to seal the cavity; and a biodegradable coating covering the sampling opening, the biodegradable coating comprising a plurality of biodegradable coating layers, the degradation of the plurality of biodegradable coating layers exposing the sampling opening to allow fluid flow into the cavity.
2. The device of claim 1 , wherein the plurality of biodegradable coating layers are disposed within the sampling opening.
3. The device of claim 2 , wherein the plurality of biodegradable coating layers are constrained within the sampling opening.
4. The device of claim 1 , wherein the plurality of biodegradable coating layers are disposed on an exterior surface of the capsule and across the sampling opening.
5. The device of any one of claims 1 to 4, wherein the plurality of biodegradable coating layers comprises a first biodegradable coating layer and a second biodegradable coating layer.
6. 6. The device of claim 5, wherein the first biodegradable coating layer comprises a first biodegradable coating layer configured to degrade at a first predetermined location in the digestive tract, and the second biodegradable coating layer comprises a second biodegradable coating layer configured to degrade at a second predetermined location in the digestive tract that is different from the first predetermined location.
7. 7. The device of claim 6, wherein the first biodegradable coating layer is configured to degrade in a small intestine of the digestive tract and the second biodegradable coating layer is configured to degrade in a large intestine of the digestive tract.
8. 6. The device of claim 5, wherein the first biodegradable coating layer is configured to degrade when exposed to a first pH level and the second biodegradable coating layer is configured to degrade when exposed to a second pH level that is different from the first pH level.
9. 9. The device of claim 8, wherein the first biodegradable coating layer is configured to degrade at a pH greater than 5.5 and the second biodegradable coating layer is configured to degrade at a pH less than 5.
5.
10. The device of claim 1 , wherein the capsule housing includes a hydrophilic coating.
11. The device of claim 10 , wherein the hydrophilic coating is formed by exposing the capsule housing to a plasma treatment followed by a polyethylene glycol treatment.
12. The device of claim 1 , wherein the sampling hydrogel is synthesized from acrylamide monomers.
13. The device of claim 1 , wherein the sampling hydrogel is synthesized from acrylic acid and acrylamide monomers.
14. 14. The device of claim 13, wherein the ratio of acrylic acid monomers to acrylamide monomers is about 10% acrylic acid monomers and about 90% acrylamide monomers.
15. The device of claim 1 , wherein the sealing member is at least partially gas permeable.
16. The device of claim 15 , wherein the sealing member is a polydimethylsiloxane membrane.
17. The device of claim 1 , wherein the capsule housing comprises a first housing portion and a second housing portion removably attachable to one another to form the capsule housing.
18. The device of claim 17 , wherein the first and second housing portions are attachable to one another via a threaded interface.
19. The device of claim 17 , wherein the sampling opening is formed in the first housing portion.
20. 10. The device of claim 1, wherein the sampling hydrogel is constructed and arranged to maintain viable bacteria present in the sample fluid viable for at least one hour after the cavity is sealed.
21. 21. The device of claim 20, wherein the sampling hydrogel is constructed and arranged to maintain viable bacteria present in the sample fluid viable for up to 24 hours after the cavity is sealed.
22. The device of claim 1 , wherein the sampling hydrogel is the only component within the capsule housing that is configured to absorb the sample fluid.
23. The device of claim 1 , wherein the sealing member is formed by solution casting.
24. The device of claim 1 , wherein the biodegradable coating is formed by solution casting.
25. The device of claim 1 , wherein the biodegradable coating is formed by drop casting.
26. 1. A method of manufacturing a device for passive sampling of the gastrointestinal tract, comprising: providing a capsule housing having a cavity and a sampling opening providing fluid communication between the cavity and an exterior of the capsule housing; and closing the sampling opening with a biodegradable coating comprising a plurality of biodegradable coating layers, wherein decomposition of the plurality of biodegradable coating layers exposes the sampling opening to allow fluid flow into the cavity.
27. 27. The method of claim 26, wherein closing the sampling opening with a plurality of biodegradable coatings comprises depositing the plurality of biodegradable coating layers into the sampling opening using a drop casting technique.
28. 28. The method of claim 27, wherein using a drop casting technique comprises: placing a first portion of the capsule housing, the first portion of the capsule housing including the sampling opening, onto a sealing plate, the sealing plate configured to provide a fluid-tight seal with the sampling opening; depositing the plurality of biodegradable coating layers within the sampling opening using a drop casting technique; and removing the first portion of the capsule housing from the sealing plate.
29. 27. The method of claim 26, further comprising drying the multiple biodegradable coating layers using near infrared radiation.
30. 27. The method of claim 26, wherein the biodegradable coating is disposed on only a portion of the capsule housing.
31. 27. The method of claim 26, wherein the biodegradable coating is disposed within the sampling opening.
32. 32. The method of claim 31 , wherein the plurality of biodegradable coating layers of the biodegradable coating are constrained within the sampling opening.
33. 27. The method of claim 26, wherein the biodegradable coating is formed as a flat surface.
34. 27. The method of claim 26, further comprising providing a sampling hydrogel within the cavity, the sampling hydrogel being configured, upon exposure to a sample fluid, to absorb the sample fluid, expand within the cavity, and store the sample fluid for subsequent analysis.
35. 27. The method of claim 26, wherein closing the sampling opening with a biodegradable coating comprising a plurality of biodegradable coating layers comprises: closing the sampling opening with a first biodegradable coating layer; drying the first biodegradable coating layer using near-infrared radiation; depositing a second biodegradable coating layer on the first biodegradable coating layer; and drying the second biodegradable coating layer using near-infrared radiation.
Citation Information
Patent Citations
Biodegradable film and laminated material
JP2016513153A
Method for producing bisphenol and method for producing polycarbonate resin
JP2020037530A
Devices and methods for collecting gastrointestinal samples
JP2021142330A
Capsule for gastrointestinal sampling
WO2021126925A1